Identification of islet cell characteristics in humans with type 2 diabetes by single‐cell sequencing. Issue 10 (4th June 2022) - Imai, Junta
Abstract : Pathologically, type 2 diabetes mellitus develops on the basis of insufficient insulin action. Insulin action insufficiency results from impaired insulin secretion and/or insulin resistance, i.e., the failure of insulin to exert sufficient effects. Impairment of insulin secretion is attributable to an insufficient pancreatic β cell mass and/or pancreatic β cell dysfunction, features collectively referred to as β cell failure. As β cell failure plays a critical role in the pathology of type 2 diabetes, strategies aimed at reversing β cell failure or preserving β cells before failure becomes evident are urgently needed. However, difficulties in conducting experiments on pancreatic β cells in vivo, especially in humans, are a major challenge impeding the development of such eagerly‐awaited therapeutic options. In a recent Journal of Clinical Investigation article, Son et al. described their efforts to identify an alteration in regulatory protein activity in human β cells, which is elicited in the state of type 2 diabetes, and explored therapeutic options for preventing β cell failure.